2013
DOI: 10.1007/s00894-013-1900-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of organic solvents and substrate binding on trypsin in acetonitrile and hexane media

Abstract: In this work, we used molecular dynamic (MD) simulation to study trypsin with and without a six-amino-acid peptide bound in three different solvents (water, acetonitrile and hexane) in order to provide molecular information for well understanding the structure and function of enzymes in non-aqueous media. The results show that the enzyme is more compact and less native-like in hexane than in the other two polar solvents. The substrate could stabilize the native protein structure in the two polar media, but not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 80 publications
0
6
0
Order By: Relevance
“…In addition, the electrostatic energy (Δ E ele ) shows as negative values, while the polar contribution to the solvation free energy (Δ E PB ) displays as positive values, which indicates that the electrostatic interactions would be offset by the unfavorable electrostatic solvation free energy. This result is expected since the electrostatic interaction is generally anti-correlated with the electrostatic solvation free energy [ 45 ].…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…In addition, the electrostatic energy (Δ E ele ) shows as negative values, while the polar contribution to the solvation free energy (Δ E PB ) displays as positive values, which indicates that the electrostatic interactions would be offset by the unfavorable electrostatic solvation free energy. This result is expected since the electrostatic interaction is generally anti-correlated with the electrostatic solvation free energy [ 45 ].…”
Section: Resultsmentioning
confidence: 93%
“…The polar contribution is calculated using PB model, and the nonpolar contribution is estimated by the solvent accessible surface area using the LCPO method. Similar to many investigations, the entropy contribution ( T Δ S ) was neglected in this study since our aim was to analyze the relative energy contribution of amino acids residues in enzyme-substrate complex formation [ 45 , 57 ]. In our study, a total of 100 frames retrieved from the last 1 ns production trajectory with an interval of 10 ps were used for the binding free energy calculation.…”
Section: Methodsmentioning
confidence: 99%
“…The results showed that acetonitrile causes deviations from the native enzyme structure and flexibility loss, and that the structure changes occurring in the active pocket weaken the catalytic H-bond network and increase the proton transfer barriers, leading to a decrease in the enzymatic activity [243]. Meng and co-workers used MD simulations to study trypsin in water, acetonitrile and hexane, and found that it is more compact and less native-like in non-polar hexane than in the other two (polar) solvents [244].…”
Section: Proteins In Non-aqueous Solventmentioning
confidence: 99%
“…QM methods complement semi-empirical MD methods, and are often restricted to the protein active site to study chemical reactions in terms of bond making and breaking, and to characterize molecular interactions at the electronic level. Simulations of trypsin demonstrated the effect of solvent environment on enzymatic structure, substrate binding, solvent distribution, and catalytic hydrogen bonding using both a substrate-free and a substrate-bound enzyme [ 140 ]. During simulations, acetonitrile strips off water molecules from the protein surface, and shows higher deviation from the crystal structure than hexane.…”
Section: Effect Of Small Molecule Interactions On Protein Structurmentioning
confidence: 99%